Dynamics Of Religious Moderation Among Generation Z In Sibolangit District, Deli Serdang Regency - Wirian, Oktrigana (Al-Fikru: Jurnal Ilmiah, 2025)
This study aims to understand the dynamics of religious moderation among Generation Z in Sibolangit District, Deli Serdang Regency. The focus of the study is directed at how Generation Z interprets the concept of religious moderation, how these values ​​​​are manifested in daily life practices, and the factors that influence the formation of moderate attitudes. This study uses a qualitative approach with a case study method, where data is collected through in-depth interviews, participant observation, and documentation. Research informants consisted of university students, school children, local community youth, as well as educational and religious leaders who interact with Generation Z in the area. The results show that Generation Z’s understanding of religious moderation is in the fairly good category, although it is still influenced by variations in educational background, family, and social environment. The practice of religious moderation is seen in interfaith interactions, participation in joint social activities, and an open attitude towards differences in belief. However, these dynamics are also influenced by challenges such as the flow of unfiltered digital information, religious content that tends to be exclusive, and the influence of peer groups. The main supporting factors arise from the role of families, schools/campuses, and social communities that encourage understanding of diversity and interfaith dialogue.